Determinants of Investment Decision Quality in Village-Owned Enterprises: The Role of Digital Literacy, Behavioral Factors, and Social Environment - Hendrik Suhendri; Agnes Quartina Pudjiastuti (Yayasan Darussalam Bengkulu, 2026)
Background: This study examines the role of digital literacy knowledge, decision-making behavior, and social environment in shaping the quality of investment decisions within Village-Owned Enterprises (BUMDes) in Malang Raya. Guided by bounded rationality theory, the research argues that limitations in information processing, cognitive capacity, and social pressures influence how BUMDes managers evaluate and select investment alternatives. Method: Using a quantitative descriptive–correlational design, data were collected through a survey of 66 BUMDes managers who met the criteria of active involvement in investment decision-making. The structural model was tested using PLS-SEM (WarpPLS). Results: Results of the measurement model confirm that all constructs meet the reliability and validity criteria. The structural findings show that digital literacy knowledge does not significantly influence decision-making behavior, yet it has a significant effect on the social environment. Both decision-making behavior and social environment demonstrate significant positive effects on the quality of BUMDes investment decisions. Conclusion: These results highlight that beyond individual cognitive capability, social norms and community expectations shape managerial investment judgment. The study contributes to the limited empirical literature on investment decision quality in BUMDes and underscores the need for strengthening digital competence and supportive social structures to enhance investment governance at the village level